2018
DOI: 10.1111/febs.14511
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of a putative glutamate 5‐kinase from Leishmania donovani

Abstract: Previous metabolic studies have demonstrated that leishmania parasites are able to synthesise proline from glutamic acid and threonine from aspartic acid. The first committed step in both biosynthetic pathways involves an amino acid kinase, either a glutamate 5‐kinase (G5K; http://www.chem.qmul.ac.uk/iubmb/enzyme/EC2/7/2/11.html) or an aspartokinase (http://www.chem.qmul.ac.uk/iubmb/enzyme/EC2/7/2/4.html). Bioinformatic analysis of multiple leishmania genomes identifies a single amino acid‐kinase gene (LdBPK 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 82 publications
(116 reference statements)
0
7
0
Order By: Relevance
“…A group of non-stressed cells followed the same protocol, but were always kept in culture medium. Importantly, such decrease in the level of free Pro should abolish the allosteric regulation Pro imposes on its biosynthetic pathway (25).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A group of non-stressed cells followed the same protocol, but were always kept in culture medium. Importantly, such decrease in the level of free Pro should abolish the allosteric regulation Pro imposes on its biosynthetic pathway (25).…”
Section: Resultsmentioning
confidence: 99%
“…In T. cruzi , Glu is also employed as energy source, but not without being first converted into Pro (via the activity of P5CS and P5CR), which is imported into the mitochondrion and catabolised in a canonical pathway (4, 10, 16). Leishmania species retain all genes necessary for a functional Pro biosynthesis pathway (70) and at least one of them (GK) has been demonstrated to be functional in Leishmania donovani (25). Here, we showed that the three enzymes involved in the anabolism of Pro from Glu are expressed at similar levels in procyclic forms of L. braziliensis , and that their expression fluctuates across life cycle stages, which might be associated with different functions played by these proteins in each life stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, recent experimental studies have reported that mutations in enzymes closely associated with arginine and glutamine pathways (Figure 7) can impede a pathogen's growth, development and infection (Aron, Wang, Lin, et al, 2021;Aron, Wang, Mabeche, et al, 2021). Third, G5K has attracted attention as a potential target in previous experimental studies involving Leishmania donovani (Sienkiewicz et al, 2018) and Mycobacterium tuberculosis (Panciera et al, 2022). Using a comprehensive broad-spectrum analysis, we found a significant homology between M. oryzae's G5K and 240 proteins from 85 distinct pathogens, in contrast to Ack, which exhibited homology with 171 proteins from 86 diverse pathogens (Figures S1 and S2).…”
Section: Discussionmentioning
confidence: 99%
“…GK activity was measured by the production of ADP in an enzyme-coupled system with pyruvate kinase (PK) and lactate dehydrogenase (LDH) [16,25]. The reaction mixture (final volume, 1 ml) contained the following: 100 mM HEPES-NaOH pH 7.4, 400 mM sodium glutamate, 5 mM ATP, 10 mM MgCl 2 , 1 mM phosphoenoylpyruvate, 0.25 mM NADH, 7.5 U PK/LDH (Sigma-Aldrich), and 2 μg of purified GK.…”
Section: Assay Of Gk Activitymentioning
confidence: 99%